An In-Depth Literature Review of E-Portfolio Implementation in Higher Education: Processes, Barriers, and Strategies - Hongyan Yang; Rachel Wong (Issues and Trends in Learning Technologies)
This literature review examines the implementation of e-portfolios in higher education, with a focus on the implementation process, potential barriers, and strategies for overcoming challenges. This review seeks to provide instructional designers and higher education instructors with design strategies to effectively implement e-portfolios. Through an analysis of seventeen studies, we identified six common steps in the implementation process, including identifying a purpose, stakeholders, and platform, conducting workshops, creating e-portfolios, and evaluating the project. The implementation process also raised eight concerns, including concerns related to technology, policy, pedagogy, artifact quality, privacy, student motivation, academic integrity, and teacher workload. To address these concerns, existing strategies suggest that successful implementation requires training and policy support, student-centered pedagogy, criteria for assessing artifacts, privacy and data protection, feedback, anti-plagiarism measures, and shared successful models.